(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
Comparative study of DNA complexes with acridine orange (AO), ethidium bromide (EtBr) and methylene blue (MB) has been carried out at 0.02 M ionic strength of solution in 0 < r ≤ 0.33, r = [ligand] / [DNA] range. The values of changes of melting parameters (δ(1/T_m) and δ(Δ T/T_m^ 2)) of these complexes were determined. From the obtained data it was revealed that the dependence of δ (1/T_m) enhances in the whole interval of change of r for three ligands, while the dependence of δ(Δ T/T_m^ 2) rises at relatively low values of r and comes out to plateau in the case of AO and MB; in the case of EtBr this dependence takes bell-like form.